Family Burden among Caregivers of Mentally ill Patients Residing in an Urban Community of Delhi: A Cross-Sectional Study - Jain, Anshika; Ray, Tapas K; Dhiman, Balraj; Laskar, Ananya Ray; Kataria, Dinesh (Indian Journal of Community Health, 2025)
Background: Family plays a pivotal role in the care of mentally ill patients. Family burden refers to the stress and strain that family members or friends experience when they take care of someone who is ill. This burden can include emotional, physical, and financial challenges. Aim & Objective: To assess the family burden among caregivers of mentally ill patients residing at Kalyanpuri, East Delhi. Settings and Design: Community based Cross-Sectional Study Design Methods and Material: A primary caregiver of mentally ill patients, who were residing at Kalyanpuri area and attending the psychiatric clinic of Lal Bahadur Shastri Hospital and Urban Health Centre Kalyanpuri, run by the Department of Community Medicine, Lady Hardinge Medical College, were interviewed using Family Burden Interview Schedule (FBIS) and Family burden among the study participants was assessed. Statistical analysis used: Data were appropriately coded and entered into the freely available SPSS version for analysis. Results: A total of 250 primary caregivers were interviewed and family burden was found in them. Nearly half (49.6%) and one third (34.4%) of the participants experienced moderate and mild level of burden respectively, with the lowest (16.0%) number of participants experiencing the severe level of burden. In different domains disruption of routine family activities had highest mean weighted score (1.13 ± 0.39). The level of burden in caregivers was significantly associated with gender of caregivers, duration of illness of the patient and time spent on caregiving (p < 0.05). Conclusions: Most of the caregivers were suffering from a moderate level, followed by mild and severe level burden.